DIPLOMASI KEBUDAYAAN INDONESIA:: ERA ORDE BARU HINGGA KINI - Rizki Dian Nursita; Ahmad Sahide (The Indonesian Islamic Studies and International Relations Association (Insiera), 2018)
Discussion and focus in the study of International Relations have been developed and influenced by the concept of diplomacy. One of the impacts of its development is the emergence of the cultural diplomacy. Cultural diplomacy has long been practiced by Indonesian government, since Indonesia gained its independence. Although the cultural diplomacy in the Old Order era had not shown any significant impact on Indonesia's national interests, cultural diplomacy always be a part of Indonesia's foreign policy. This paper aims to provide an overview, comparison and evaluation of cultural diplomacy in Indonesia from the New Order era until post-reform. Through the analysis of a number of literatures, authors found that Indonesia cultural diplomacy in the New Order era carried to short-term interests; whether economic or development interest manifested in exhibitions, cooperations and international forums, as well as competitions; and still lack of political or cultural interest. However, Indonesia post-reform cultural diplomacy has encouraged the involvement of non-state actors as well as the performance of public and digital diplomacy.